Magnetic nanobiosorbent (MG‐Chi/Fe3O4) for dispersive solid‐phase extraction of Cu(II), Pb(II), and Cd(II) followed by flame atomic absorption spectrometry determination - Narges Salehi; Ali Moghimi; Hamidreza Shahbazi (IET Nanobiotechnology, 2021)
Abstract Trace amounts of Cu (II), Pb (II), and Cd (II) in a wastewater sample were preconcentrated with a novel cross‐linked magnetic chitosan modified with a new synthesised methionine‐glutaraldehyde Schiff's base (MG‐Chi/Fe3O4) as a dispersive solid‐phase extraction (DSPE) adsorbent. The adsorbed metal ions were then eluted with a specific volume of suitable solution and determined by flame atomic absorption spectrometry (FAAS). Various parameters affecting the extraction efficiency of the metal ions were investigated and optimised, including pH, amount of adsorbent, extraction time, type and volume rate of eluent, elution time, sample volume, and effect of interfering ions. The adsorption kinetics are more consistent with the pseudo‐second order model. The results were statistically interpreted and the analytical performance of the proposed method was found to have preconcentration factors of 55, 60, and 50 μg L−1 for Cu(II), Pb(II), and Cd(II), respectively, limits of detection were 0.22, 0.24, and 0.10 μg L−1 for Cu(II), Pb(II), and Cd(II), respectively, with a relative standard deviation (1.5%‐2.8 %), and the liner range was 5–1000 for Cu(II) and Pb(II) and 2.5–1000 for Cd(II). It was concluded that this method was suitable for successful simultaneous determination of Cu(II), Pb(II), and Cd(II) in industrial wastewater samples.